# Translations of classical logic

(diff) ← Older revision | Latest revision (diff) | Newer revision → (diff)

## T-translation $A\imp B \mapsto \oc{\wn{A}}\limp\wn{B}$

Formulas are translated as: $\begin{array}{rcl} X^T & = & X \\ (A\imp B)^T & = & \oc{\wn{A^T}}\limp\wn{B^T} \\ (A\wedge B)^T & = & \wn{A^T} \with \wn{B^T} \\ T^T & = & \top \\ (A\vee B)^T & = & \wn{A^T}\parr\wn{B^T} \\ F^T & = & \bot \\ (\neg A)^T & = & \wn{\oc{(A^T)\orth}} \\ (\forall\xi A)^T & = & \forall\xi \wn{A^T} \\ (\exists\xi A)^T & = & \exists\xi \oc{\wn{A^T}} \end{array}$

This is extended to sequents by $(\Gamma\vdash\Delta)^T = \oc{\wn{\Gamma^T}}\vdash\wn{\Delta^T}$.

This allows one to translate the rules of classical logic into linear logic: $\LabelRule{\rulename{ax}} \NulRule{A\vdash A} \DisplayProof \qquad\mapsto\qquad \LabelRule{\rulename{ax}} \NulRule{\wn{A^T}\vdash\wn{A^T}} \LabelRule{\oc L} \UnaRule{\oc{\wn{A^T}}\vdash\wn{A^T}} \DisplayProof$ $\AxRule{\Gamma\vdash A,\Delta} \AxRule{\Gamma',A\vdash\Delta'} \LabelRule{\rulename{cut}} \BinRule{\Gamma,\Gamma'\vdash\Delta,\Delta'} \DisplayProof \qquad\mapsto\qquad \AxRule{\oc{\wn{\Gamma^T}}\vdash\wn{A^T},\wn{\Delta^T}} \LabelRule{\oc R} \UnaRule{\oc{\wn{\Gamma^T}}\vdash\oc{\wn{A^T}},\wn{\Delta^T}} \AxRule{\oc{\wn{\Gamma'^T}},\oc{\wn{A^T}}\vdash\wn{\Delta'^T}} \LabelRule{\rulename{cut}} \BinRule{\oc{\wn{\Gamma^T}},\oc{\wn{\Gamma'^T}}\vdash\wn{\Delta^T},\wn{\Delta'^T}} \DisplayProof$ $\AxRule{\Gamma,A,A\vdash\Delta} \LabelRule{c L} \UnaRule{\Gamma,A\vdash\Delta} \DisplayProof \qquad\mapsto\qquad \AxRule{\oc{\wn{\Gamma^T}},\oc{\wn{A^T}},\oc{\wn{A^T}}\vdash\wn{\Delta^T}} \LabelRule{\oc c L} \UnaRule{\oc{\wn{\Gamma^T}},\oc{\wn{A^T}}\vdash\wn{\Delta^T}} \DisplayProof$ $\AxRule{\Gamma\vdash A,A,\Delta} \LabelRule{c R} \UnaRule{\Gamma\vdash A,\Delta} \DisplayProof \qquad\mapsto\qquad \AxRule{\oc{\wn{\Gamma^T}}\vdash\wn{A^T},\wn{A^T},\wn{\Delta^T}} \LabelRule{\wn c R} \UnaRule{\oc{\wn{\Gamma^T}}\vdash\wn{A^T},\wn{\Delta^T}} \DisplayProof$ $\AxRule{\Gamma\vdash\Delta} \LabelRule{w L} \UnaRule{\Gamma,A\vdash\Delta} \DisplayProof \qquad\mapsto\qquad \AxRule{\oc{\wn{\Gamma^T}}\vdash\wn{\Delta^T}} \LabelRule{\oc w L} \UnaRule{\oc{\wn{\Gamma^T}},\oc{\wn{A^T}}\vdash\wn{\Delta^T}} \DisplayProof$ $\AxRule{\Gamma\vdash\Delta} \LabelRule{w R} \UnaRule{\Gamma\vdash A,\Delta} \DisplayProof \qquad\mapsto\qquad \AxRule{\oc{\wn{\Gamma^T}}\vdash\wn{\Delta^T}} \LabelRule{\wn w R} \UnaRule{\oc{\wn{\Gamma^T}}\vdash\wn{A^T},\wn{\Delta^T}} \DisplayProof$ $\AxRule{\Gamma,A\vdash B,\Delta} \LabelRule{\imp R} \UnaRule{\Gamma\vdash A\imp B,\Delta} \DisplayProof \qquad\mapsto\qquad \AxRule{\oc{\wn{\Gamma^T}},\oc{\wn{A^T}}\vdash\wn{B^T},\wn{\Delta^T}} \LabelRule{\limp R} \UnaRule{\oc{\wn{\Gamma^T}}\vdash \oc{\wn{A^T}}\limp\wn{B^T},\wn{\Delta^T}} \LabelRule{\wn d R} \UnaRule{\oc{\wn{\Gamma^T}}\vdash \wn{(\oc{\wn{A^T}}\limp\wn{B^T})},\wn{\Delta^T}} \DisplayProof$ $\AxRule{\Gamma\vdash A,\Delta} \AxRule{\Gamma',B\vdash\Delta'} \LabelRule{\imp L} \BinRule{\Gamma,\Gamma',A\imp B\vdash\Delta,\Delta'} \DisplayProof \qquad\mapsto\qquad \AxRule{\oc{\wn{\Gamma^T}}\vdash\wn{A^T},\wn{\Delta^T}} \LabelRule{\oc R} \UnaRule{\oc{\wn{\Gamma^T}}\vdash\oc{\wn{A^T}},\wn{\Delta^T}} \LabelRule{\rulename{ax}} \NulRule{\wn{B^T}\vdash\wn{B^T}} \LabelRule{\limp L} \BinRule{\oc{\wn{\Gamma^T}},\oc{\wn{A^T}}\limp\wn{B^T}\vdash\wn{B^T},\wn{\Delta^T}} \LabelRule{\wn L} \UnaRule{\oc{\wn{\Gamma^T}},\wn{(\oc{\wn{A^T}}\limp\wn{B^T})}\vdash\wn{B^T},\wn{\Delta^T}} \LabelRule{\oc d L} \UnaRule{\oc{\wn{\Gamma^T}},\oc{\wn{(\oc{\wn{A^T}}\limp\wn{B^T})}}\vdash\wn{B^T},\wn{\Delta^T}} \LabelRule{\oc R} \UnaRule{\oc{\wn{\Gamma^T}},\oc{\wn{(\oc{\wn{A^T}}\limp\wn{B^T})}}\vdash\oc{\wn{B^T}},\wn{\Delta^T}} \AxRule{\oc{\wn{\Gamma'^T}},\oc{\wn{B^T}}\vdash\wn{\Delta'^T}} \LabelRule{\rulename{cut}} \BinRule{\oc{\wn{\Gamma^T}},\oc{\wn{\Gamma'^T}},\oc{\wn{(\oc{\wn{A^T}}\limp\wn{B^T})}}\vdash\wn{\Delta^T},\wn{\Delta'^T}} \DisplayProof$ $\AxRule{\Gamma\vdash A,\Delta} \AxRule{\Gamma\vdash B,\Delta} \LabelRule{\wedge R} \BinRule{\Gamma\vdash A\wedge B,\Delta} \DisplayProof \qquad\mapsto\qquad \AxRule{\oc{\wn{\Gamma^T}}\vdash \wn{A^T},\wn{\Delta^T}} \AxRule{\oc{\wn{\Gamma^T}}\vdash \wn{B^T},\wn{\Delta^T}} \LabelRule{\with R} \BinRule{\oc{\wn{\Gamma^T}}\vdash \wn{A^T}\with \wn{B^T},\wn{\Delta^T}} \LabelRule{\wn d R} \UnaRule{\oc{\wn{\Gamma^T}}\vdash \wn{(\wn{A^T}\with \wn{B^T})},\wn{\Delta^T}} \DisplayProof$ $\AxRule{\Gamma,A\vdash \Delta} \LabelRule{\wedge_1 L} \UnaRule{\Gamma,A\wedge B\vdash \Delta} \DisplayProof \qquad\mapsto\qquad \LabelRule{\rulename{ax}} \NulRule{\wn{A^T}\vdash \wn{A^T}} \LabelRule{\with_1 L} \UnaRule{\wn{A^T}\with \wn{B^T}\vdash \wn{A^T}} \LabelRule{\wn L} \UnaRule{\wn{(\wn{A^T}\with \wn{B^T})}\vdash \wn{A^T}} \LabelRule{\oc d L} \UnaRule{\oc{\wn{(\wn{A^T}\with \wn{B^T})}}\vdash \wn{A^T}} \LabelRule{\oc R} \UnaRule{\oc{\wn{(\wn{A^T}\with \wn{B^T})}}\vdash \oc{\wn{A^T}}} \AxRule{\oc{\wn{\Gamma^T}},\oc{\wn{A^T}}\vdash \wn{\Delta^T}} \LabelRule{\rulename{cut}} \BinRule{\oc{\wn{\Gamma^T}},\oc{\wn{(\wn{A^T}\with \wn{B^T})}}\vdash \wn{\Delta^T}} \DisplayProof$ $\LabelRule{T R} \NulRule{\Gamma\vdash T,\Delta} \DisplayProof \qquad\mapsto\qquad \LabelRule{\top R} \NulRule{\oc{\wn{\Gamma^T}}\vdash \top,\wn{\Delta^T}} \LabelRule{\wn d R} \UnaRule{\oc{\wn{\Gamma^T}}\vdash \wn{\top},\wn{\Delta^T}} \DisplayProof$ $\AxRule{\Gamma\vdash A,B,\Delta} \LabelRule{\vee R} \UnaRule{\Gamma\vdash A\vee B,\Delta} \DisplayProof \qquad\mapsto\qquad \AxRule{\oc{\wn{\Gamma^T}}\vdash \wn{A^T},\wn{B^T},\wn{\Delta^T}} \LabelRule{\parr R} \UnaRule{\oc{\wn{\Gamma^T}}\vdash \wn{A^T}\parr\wn{B^T},\wn{\Delta^T}} \LabelRule{\wn d R} \UnaRule{\oc{\wn{\Gamma^T}}\vdash \wn{(\wn{A^T}\parr\wn{B^T})},\wn{\Delta^T}} \DisplayProof$ $\AxRule{\Gamma,A\vdash \Delta} \AxRule{\Gamma',B\vdash \Delta'} \LabelRule{\vee L} \BinRule{\Gamma,\Gamma',A\vee B\vdash \Delta,\Delta'} \DisplayProof \qquad\mapsto\qquad \LabelRule{\rulename{ax}} \NulRule{\wn{A^T}\vdash \wn{A^T}} \LabelRule{\rulename{ax}} \NulRule{\wn{B^T}\vdash \wn{B^T}} \LabelRule{\parr L} \BinRule{\wn{A^T}\parr \wn{B^T}\vdash \wn{A^T},\wn{B^T}} \LabelRule{\wn L} \UnaRule{\wn{(\wn{A^T}\parr \wn{B^T})}\vdash \wn{A^T},\wn{B^T}} \LabelRule{\oc d L} \UnaRule{\oc{\wn{(\wn{A^T}\parr \wn{B^T})}}\vdash \wn{A^T},\wn{B^T}} \LabelRule{\oc R} \UnaRule{\oc{\wn{(\wn{A^T}\parr \wn{B^T})}}\vdash \wn{A^T},\oc{\wn{B^T}}} \AxRule{\oc{\wn{\Gamma'^T}},\oc{\wn{B^T}}\vdash \wn{\Delta'^T}} \LabelRule{\rulename{cut}} \BinRule{\oc{\wn{\Gamma'^T}},\oc{\wn{(\wn{A^T}\parr \wn{B^T})}}\vdash \wn{A^T},\wn{\Delta'^T}} \LabelRule{\oc R} \UnaRule{\oc{\wn{\Gamma'^T}},\oc{\wn{(\wn{A^T}\parr \wn{B^T})}}\vdash \oc{\wn{A^T}},\wn{\Delta'^T}} \AxRule{\oc{\wn{\Gamma^T}},\oc{\wn{A^T}}\vdash \wn{\Delta^T}} \LabelRule{\rulename{cut}} \BinRule{\oc{\wn{\Gamma^T}},\oc{\wn{\Gamma'^T}},\oc{\wn{(\wn{A^T}\parr \wn{B^T})}}\vdash \wn{\Delta^T},\wn{\Delta'^T}} \DisplayProof$ $\AxRule{\Gamma\vdash \Delta} \LabelRule{F R} \UnaRule{\Gamma\vdash F,\Delta} \DisplayProof \qquad\mapsto\qquad \AxRule{\oc{\wn{\Gamma^T}}\vdash \wn{\Delta^T}} \LabelRule{\bot R} \UnaRule{\oc{\wn{\Gamma^T}}\vdash \bot,\wn{\Delta^T}} \LabelRule{\wn R} \UnaRule{\oc{\wn{\Gamma^T}}\vdash \wn{\bot},\wn{\Delta^T}} \DisplayProof$ $\LabelRule{F L} \NulRule{F\vdash {}} \DisplayProof \qquad\mapsto\qquad \LabelRule{\bot L} \NulRule{\bot\vdash {}} \LabelRule{\wn L} \UnaRule{\wn{\bot}\vdash {}} \LabelRule{\oc d L} \UnaRule{\oc{\wn{\bot}}\vdash {}} \DisplayProof$ $\AxRule{\Gamma,A\vdash \Delta} \LabelRule{\neg R} \UnaRule{\Gamma\vdash \neg A,\Delta} \DisplayProof \qquad\mapsto\qquad \AxRule{\oc{\wn{\Gamma^T}},\oc{\wn{A^T}}\vdash \wn{\Delta^T}} \LabelRule{(.)\orth R} \UnaRule{\oc{\wn{\Gamma^T}}\vdash \wn{\oc{(A^T)\orth}},\wn{\Delta^T}} \LabelRule{\wn d R} \UnaRule{\oc{\wn{\Gamma^T}}\vdash \wn{\wn{\oc{(A^T)\orth}}},\wn{\Delta^T}} \DisplayProof$ $\AxRule{\Gamma\vdash A,\Delta} \LabelRule{\neg L} \UnaRule{\Gamma,\neg A\vdash \Delta} \DisplayProof \qquad\mapsto\qquad \AxRule{\oc{\wn{\Gamma^T}}\vdash \wn{A^T},\wn{\Delta^T}} \LabelRule{(.)\orth L} \UnaRule{\oc{\wn{\Gamma^T}},\oc{(A^T)\orth}\vdash \wn{\Delta^T}} \LabelRule{\wn L} \UnaRule{\oc{\wn{\Gamma^T}},\wn{\oc{(A^T)\orth}}\vdash \wn{\Delta^T}} \LabelRule{\wn L} \UnaRule{\oc{\wn{\Gamma^T}},\wn{\wn{\oc{(A^T)\orth}}}\vdash \wn{\Delta^T}} \LabelRule{\oc d L} \UnaRule{\oc{\wn{\Gamma^T}},\oc{\wn{\wn{\oc{(A^T)\orth}}}}\vdash \wn{\Delta^T}} \DisplayProof$ $\AxRule{\Gamma\vdash A,\Delta} \LabelRule{\forall R} \UnaRule{\Gamma\vdash \forall\xi A,\Delta} \DisplayProof \qquad\mapsto\qquad \AxRule{\oc{\wn{\Gamma^T}}\vdash \wn{A^T},\wn{\Delta^T}} \LabelRule{\forall R} \UnaRule{\oc{\wn{\Gamma^T}}\vdash \forall\xi \wn{A^T},\wn{\Delta^T}} \LabelRule{\wn d R} \UnaRule{\oc{\wn{\Gamma^T}}\vdash \wn{\forall\xi \wn{A^T}},\wn{\Delta^T}} \DisplayProof$ $\AxRule{\Gamma,A[\tau/\xi]\vdash \Delta} \LabelRule{\forall L} \UnaRule{\Gamma,\forall\xi A\vdash \Delta} \DisplayProof \qquad\mapsto\qquad \LabelRule{\rulename{ax}} \NulRule{\wn{A^T}[\tau^T/\xi]\vdash \wn{A^T}[\tau^T/\xi]} \LabelRule{\forall L} \UnaRule{\forall\xi \wn{A^T}\vdash \wn{A^T}[\tau^T/\xi]} \LabelRule{\wn L} \UnaRule{\wn{\forall\xi \wn{A^T}}\vdash \wn{A^T}[\tau^T/\xi]} \LabelRule{\oc d L} \UnaRule{\oc{\wn{\forall\xi \wn{A^T}}}\vdash \wn{A^T}[\tau^T/\xi]} \LabelRule{\oc R} \UnaRule{\oc{\wn{\forall\xi \wn{A^T}}}\vdash \oc{\wn{A^T}}[\tau^T/\xi]} \AxRule{\oc{\wn{\Gamma^T}},\oc{\wn{(A^T[\tau^T/\xi])}}\vdash \wn{\Delta^T}} \LabelRule{\rulename{cut}} \BinRule{\oc{\wn{\Gamma^T}},\oc{\wn{\forall\xi \wn{A^T}}}\vdash \wn{\Delta^T}} \DisplayProof$ $\AxRule{\Gamma\vdash A[\tau/\xi],\Delta} \LabelRule{\exists R} \UnaRule{\Gamma\vdash \exists\xi A,\Delta} \DisplayProof \qquad\mapsto\qquad \AxRule{\oc{\wn{\Gamma^T}}\vdash \wn{A^T[\tau^T/\xi]},\wn{\Delta^T}} \LabelRule{\oc R} \UnaRule{\oc{\wn{\Gamma^T}}\vdash \oc{\wn{A^T[\tau^T/\xi]}},\wn{\Delta^T}} \LabelRule{\exists R} \UnaRule{\oc{\wn{\Gamma^T}}\vdash \exists\xi \oc{\wn{A^T}},\wn{\Delta^T}} \LabelRule{\wn d R} \UnaRule{\oc{\wn{\Gamma^T}}\vdash \wn{\exists\xi \oc{\wn{A^T}}},\wn{\Delta^T}} \DisplayProof$ $\AxRule{\Gamma,A\vdash \Delta} \LabelRule{\exists L} \UnaRule{\Gamma,\exists\xi A\vdash \Delta} \DisplayProof \qquad\mapsto\qquad \AxRule{\oc{\wn{\Gamma^T}},\oc{\wn{A^T}}\vdash \wn{\Delta^T}} \LabelRule{\exists L} \UnaRule{\oc{\wn{\Gamma^T}},\exists\xi\oc{\wn{A^T}}\vdash \wn{\Delta^T}} \LabelRule{\wn L} \UnaRule{\oc{\wn{\Gamma^T}},\wn{\exists\xi\oc{\wn{A^T}}}\vdash \wn{\Delta^T}} \LabelRule{\oc d L} \UnaRule{\oc{\wn{\Gamma^T}},\oc{\wn{\exists\xi\oc{\wn{A^T}}}}\vdash \wn{\Delta^T}} \DisplayProof$

### Alternative presentation

It is also possible to define $A^{\overline{T}}$ by: $\begin{array}{rcl} X^{\overline{T}} & = & \wn{X} \\ (A\imp B)^{\overline{T}} & = & \wn{(\oc{A^{\overline{T}}}\limp B^{\overline{T}})} \\ (A\wedge B)^{\overline{T}} & = & \wn{(A^{\overline{T}} \with B^{\overline{T}})} \\ T^{\overline{T}} & = & \wn{\top} \\ (A\vee B)^{\overline{T}} & = & \wn{(A^{\overline{T}}\parr B^{\overline{T}})} \\ F^{\overline{T}} & = & \wn{\bot} \\ (\neg A)^{\overline{T}} & = & \wn{\wn{(A^{\overline{T}})\orth}} \\ (\forall\xi A)^{\overline{T}} & = & \wn{\forall\xi A^{\overline{T}}} \\ (\exists\xi A)^{\overline{T}} & = & \wn{\exists\xi \oc{A^{\overline{T}}}} \end{array}$

If we define $(\Gamma\vdash\Delta)^{\overline{T}} = \oc{\Gamma^{\overline{T}}}\vdash \Delta^{\overline{T}}$, we have $(\Gamma\vdash\Delta)^{\overline{T}} = (\Gamma\vdash\Delta)^T$ and thus we obtain the same translation of proofs.

## Q-translation $A\imp B \mapsto \oc{(A\limp\wn{B})}$

Formulas are translated as: $\begin{array}{rcl} X^Q & = & \oc{X} \\ (A\imp B)^Q & = & \oc{(A^Q\limp\wn{B^Q})} \\ (A\wedge B)^Q & = & \oc{(A^Q \tens B^Q)} \\ T^Q & = & \oc{\one} \\ (A\vee B)^Q & = & \oc{(A^Q\plus B^Q)} \\ F^Q & = & \oc{\zero} \\ (\neg A)^Q & = & \oc{(A^Q)\orth} \\ (\forall\xi A)^Q & = & \oc{\forall\xi \wn{A^Q}} \\ (\exists\xi A)^Q & = & \oc{\exists\xi A^Q} \end{array}$

The translation of any formula starts with $\oc$, we define $A^{\underline{Q}}$ such that $A^Q=\oc{A^{\underline{Q}}}$.

The translation of sequents is $(\Gamma\vdash\Delta)^Q = \Gamma^Q\vdash\wn{\Delta^Q}$.

This allows one to translate the rules of classical logic into linear logic: $\LabelRule{\rulename{ax}} \NulRule{A\vdash A} \DisplayProof \qquad\mapsto\qquad \LabelRule{\rulename{ax}} \NulRule{A^Q\vdash A^Q} \LabelRule{\wn d R} \UnaRule{A^Q\vdash \wn{A^Q}} \DisplayProof$ $\AxRule{\Gamma\vdash A,\Delta} \AxRule{\Gamma',A\vdash \Delta'} \LabelRule{\rulename{cut}} \BinRule{\Gamma,\Gamma'\vdash \Delta,\Delta'} \DisplayProof \qquad\mapsto\qquad \AxRule{\Gamma^Q\vdash \wn{A^Q},\wn{\Delta^Q}} \AxRule{\Gamma'^Q,A^Q\vdash \wn{\Delta'^Q}} \LabelRule{\wn L} \UnaRule{\Gamma'^Q,\wn{A^Q}\vdash \wn{\Delta'^Q}} \LabelRule{\rulename{cut}} \BinRule{\Gamma^Q,\Gamma'^Q\vdash \wn{\Delta^Q},\wn{\Delta'^Q}} \DisplayProof$ $\AxRule{\Gamma,A,A\vdash \Delta} \LabelRule{c L} \UnaRule{\Gamma,A\vdash \Delta} \DisplayProof \qquad\mapsto\qquad \AxRule{\Gamma^Q,A^Q,A^Q\vdash \wn{\Delta^Q}} \LabelRule{\oc c L} \UnaRule{\Gamma^Q,A^Q\vdash \wn{\Delta^Q}} \DisplayProof$ $\AxRule{\Gamma\vdash A,A,\Delta} \LabelRule{c R} \UnaRule{\Gamma\vdash A,\Delta} \DisplayProof \qquad\mapsto\qquad \AxRule{\Gamma^Q\vdash \wn{A^Q},\wn{A^Q},\wn{\Delta^Q}} \LabelRule{\wn c R} \UnaRule{\Gamma^Q\vdash \wn{A^Q},\wn{\Delta^Q}} \DisplayProof$ $\AxRule{\Gamma\vdash \Delta} \LabelRule{w L} \UnaRule{\Gamma,A\vdash \Delta} \DisplayProof \qquad\mapsto\qquad \AxRule{\Gamma^Q\vdash \wn{\Delta^Q}} \LabelRule{\oc w L} \UnaRule{\Gamma^Q,A^Q\vdash \wn{\Delta^Q}} \DisplayProof$ $\AxRule{\Gamma\vdash \Delta} \LabelRule{w R} \UnaRule{\Gamma\vdash A,\Delta} \DisplayProof \qquad\mapsto\qquad \AxRule{\Gamma^Q\vdash \wn{\Delta^Q}} \LabelRule{\wn w R} \UnaRule{\Gamma^Q\vdash \wn{A^Q},\wn{\Delta^Q}} \DisplayProof$ $\AxRule{\Gamma,A\vdash B,\Delta} \LabelRule{\imp R} \UnaRule{\Gamma\vdash A\imp B,\Delta} \DisplayProof \qquad\mapsto\qquad \AxRule{\Gamma^Q,A^Q\vdash \wn{B^Q},\wn{\Delta^Q}} \LabelRule{\limp R} \UnaRule{\Gamma^Q\vdash A^Q\limp \wn{B^Q},\wn{\Delta^Q}} \LabelRule{\oc R} \UnaRule{\Gamma^Q\vdash \oc{(A^Q\limp \wn{B^Q})},\wn{\Delta^Q}} \LabelRule{\wn d R} \UnaRule{\Gamma^Q\vdash \wn{\oc{(A^Q\limp \wn{B^Q})}},\wn{\Delta^Q}} \DisplayProof$ $\AxRule{\Gamma\vdash A,\Delta} \AxRule{\Gamma',B\vdash \Delta'} \LabelRule{\imp L} \BinRule{\Gamma,\Gamma',A\imp B\vdash \Delta,\Delta'} \DisplayProof \qquad\mapsto\qquad \AxRule{\Gamma^Q\vdash \wn{A^Q},\wn{\Delta^Q}} \LabelRule{\rulename{ax}} \NulRule{A^Q\vdash A^Q} \AxRule{\Gamma'^Q,B^Q\vdash \wn{\Delta'^Q}} \LabelRule{\wn L} \UnaRule{\Gamma'^Q,\wn{B^Q}\vdash \wn{\Delta'^Q}} \LabelRule{\limp L} \BinRule{\Gamma'^Q,A^Q\limp \wn{B^Q},A^Q\vdash \wn{\Delta'^Q}} \LabelRule{\oc d L} \UnaRule{\Gamma'^Q,\oc{(A^Q\limp \wn{B^Q})},A^Q\vdash \wn{\Delta'^Q}} \LabelRule{\wn L} \UnaRule{\Gamma'^Q,\oc{(A^Q\limp \wn{B^Q})},\wn{A^Q}\vdash \wn{\Delta'^Q}} \LabelRule{\rulename{cut}} \BinRule{\Gamma^Q,\Gamma'^Q,\oc{(A^Q\limp \wn{B^Q})}\vdash \wn{\Delta^Q},\wn{\Delta'^Q}} \DisplayProof$ $\AxRule{\Gamma\vdash A,\Delta} \AxRule{\Gamma'\vdash B,\Delta'} \LabelRule{\wedge R} \BinRule{\Gamma,\Gamma'\vdash A\wedge B,\Delta,\Delta'} \DisplayProof \qquad\mapsto\qquad \AxRule{\Gamma^Q\vdash \wn{A^Q},\wn{\Delta^Q}} \AxRule{\Gamma'^Q\vdash \wn{B^Q},\wn{\Delta'^Q}} \LabelRule{\rulename{ax}} \NulRule{A^Q\vdash A^Q} \LabelRule{\rulename{ax}} \NulRule{B^Q\vdash B^Q} \LabelRule{\tens R} \BinRule{A^Q,B^Q\vdash A^Q\tens B^Q} \LabelRule{\oc R} \UnaRule{A^Q,B^Q\vdash \oc{(A^Q\tens B^Q)}} \LabelRule{\wn d R} \UnaRule{A^Q,B^Q\vdash \wn{\oc{(A^Q\tens B^Q)}}} \LabelRule{\wn L} \UnaRule{A^Q,\wn{B^Q}\vdash \wn{\oc{(A^Q\tens B^Q)}}} \LabelRule{\rulename{cut}} \BinRule{\Gamma'^Q,A^Q\vdash \wn{\oc{(A^Q\tens B^Q)}},\wn{\Delta'^Q}} \LabelRule{\wn L} \UnaRule{\Gamma'^Q,\wn{A^Q}\vdash \wn{\oc{(A^Q\tens B^Q)}},\wn{\Delta'^Q}} \LabelRule{\rulename{cut}} \BinRule{\Gamma^Q,\Gamma'^Q\vdash \wn{\oc{(A^Q\tens B^Q)}},\wn{\Delta^Q},\wn{\Delta'^Q}} \DisplayProof$ $\AxRule{\Gamma,A,B\vdash \Delta} \LabelRule{\wedge L} \UnaRule{\Gamma,A\wedge B\vdash \Delta} \DisplayProof \qquad\mapsto\qquad \AxRule{\Gamma^Q,A^Q,B^Q\vdash \wn{\Delta^Q}} \LabelRule{\tens L} \UnaRule{\Gamma^Q,A^Q\tens B^Q\vdash \wn{\Delta^Q}} \LabelRule{\oc d L} \UnaRule{\Gamma^Q,\oc{(A^Q\tens B^Q)}\vdash \wn{\Delta^Q}} \DisplayProof$ $\LabelRule{T R} \NulRule{{}\vdash T} \DisplayProof \qquad\mapsto\qquad \LabelRule{\one R} \NulRule{{}\vdash \one} \LabelRule{\oc R} \UnaRule{{}\vdash \oc{\one}} \LabelRule{\wn d R} \UnaRule{{}\vdash \wn{\oc{\one}}} \DisplayProof$ $\AxRule{\Gamma\vdash \Delta} \LabelRule{T L} \UnaRule{\Gamma,T\vdash \Delta} \DisplayProof \qquad\mapsto\qquad \AxRule{\Gamma^Q\vdash \wn{\Delta^Q}} \LabelRule{\one L} \UnaRule{\Gamma^Q,\one\vdash \wn{\Delta^Q}} \LabelRule{\oc d L} \UnaRule{\Gamma^Q,\oc{\one}\vdash \wn{\Delta^Q}} \DisplayProof$ $\AxRule{\Gamma\vdash A,\Delta} \LabelRule{\vee_1 R} \UnaRule{\Gamma\vdash A\vee B,\Delta} \DisplayProof \qquad\mapsto\qquad \AxRule{\Gamma^Q\vdash \wn{A^Q},\wn{\Delta^Q}} \LabelRule{\rulename{ax}} \NulRule{A^Q\vdash A^Q} \LabelRule{\plus_1 R} \UnaRule{A^Q\vdash A^Q\plus B^Q} \LabelRule{\oc R} \UnaRule{A^Q\vdash \oc{(A^Q\plus B^Q)}} \LabelRule{\wn d R} \UnaRule{A^Q\vdash \wn{\oc{(A^Q\plus B^Q)}}} \LabelRule{\wn L} \UnaRule{\wn{A^Q}\vdash \wn{\oc{(A^Q\plus B^Q)}}} \LabelRule{\rulename{cut}} \BinRule{\Gamma^Q\vdash \wn{\oc{(A^Q\plus B^Q)}},\wn{\Delta^Q}} \DisplayProof$ $\AxRule{\Gamma,A\vdash \Delta} \AxRule{\Gamma,B\vdash \Delta} \LabelRule{\vee L} \BinRule{\Gamma,A\vee B\vdash \Delta} \DisplayProof \qquad\mapsto\qquad \AxRule{\Gamma^Q,A^Q\vdash \wn{\Delta^Q}} \AxRule{\Gamma^Q,B^Q\vdash \wn{\Delta^Q}} \LabelRule{\plus L} \BinRule{\Gamma^Q,A^Q\plus B^Q\vdash \wn{\Delta^Q}} \LabelRule{\oc d L} \UnaRule{\Gamma^Q,\oc{(A^Q\plus B^Q)}\vdash \wn{\Delta^Q}} \DisplayProof$ $\LabelRule{F L} \NulRule{\Gamma,F\vdash \Delta} \DisplayProof \qquad\mapsto\qquad \LabelRule{\zero L} \NulRule{\Gamma^Q,\zero\vdash \wn{\Delta^Q}} \LabelRule{\oc d L} \UnaRule{\Gamma^Q,\oc{\zero}\vdash \wn{\Delta^Q}} \DisplayProof$ $\AxRule{\Gamma,A\vdash \Delta} \LabelRule{\neg R} \UnaRule{\Gamma\vdash \neg A,\Delta} \DisplayProof \qquad\mapsto\qquad \AxRule{\Gamma^Q,A^Q\vdash \wn{\Delta^Q}} \LabelRule{(.)\orth R} \UnaRule{\Gamma^Q\vdash (A^Q)\orth,\wn{\Delta^Q}} \LabelRule{\oc R} \UnaRule{\Gamma^Q\vdash \oc{(A^Q)\orth},\wn{\Delta^Q}} \LabelRule{\wn d R} \UnaRule{\Gamma^Q\vdash \wn{\oc{(A^Q)\orth}},\wn{\Delta^Q}} \DisplayProof$ $\AxRule{\Gamma\vdash A,\Delta} \LabelRule{\neg L} \UnaRule{\Gamma,\neg A\vdash \Delta} \DisplayProof \qquad\mapsto\qquad \AxRule{\Gamma^Q\vdash \wn{A^Q},\wn{\Delta^Q}} \LabelRule{(.)\orth L} \UnaRule{\Gamma^Q,\oc{(A^Q)\orth}\vdash \wn{\Delta^Q}} \DisplayProof$ $\AxRule{\Gamma\vdash A,\Delta} \LabelRule{\forall R} \UnaRule{\Gamma\vdash \forall\xi A,\Delta} \DisplayProof \qquad\mapsto\qquad \AxRule{\Gamma^Q\vdash \wn{A^Q},\wn{\Delta^Q}} \LabelRule{\forall R} \UnaRule{\Gamma^Q\vdash \forall\xi \wn{A^Q},\wn{\Delta^Q}} \LabelRule{\oc R} \UnaRule{\Gamma^Q\vdash \oc{\forall\xi \wn{A^Q}},\wn{\Delta^Q}} \DisplayProof$

We use $(A[\tau/\xi])^Q=A^Q[\tau^{\underline{Q}}/\xi]$. $\AxRule{\Gamma,A[\tau/\xi]\vdash \Delta} \LabelRule{\forall L} \UnaRule{\Gamma,\forall\xi A\vdash \Delta} \DisplayProof \qquad\mapsto\qquad \AxRule{\Gamma^Q,A^Q[\tau^{\underline{Q}}/\xi]\vdash \wn{\Delta^Q}} \LabelRule{\wn L} \UnaRule{\Gamma^Q,\wn{A^Q[\tau^{\underline{Q}}/\xi]}\vdash \wn{\Delta^Q}} \LabelRule{\forall L} \UnaRule{\Gamma^Q,\forall\xi \wn{A^Q}\vdash \wn{\Delta^Q}} \LabelRule{\oc d L} \UnaRule{\Gamma^Q,\oc{\forall\xi \wn{A^Q}}\vdash \wn{\Delta^Q}} \DisplayProof$ $\AxRule{\Gamma\vdash A[\tau/\xi],\Delta} \LabelRule{\exists R} \UnaRule{\Gamma\vdash \exists\xi A,\Delta} \DisplayProof \qquad\mapsto\qquad \AxRule{\Gamma^Q\vdash \wn{A^Q[\tau^{\underline{Q}}/\xi]},\wn{\Delta^Q}} \LabelRule{\rulename{ax}} \NulRule{A^Q[\tau^{\underline{Q}}/\xi]\vdash A^Q[\tau^{\underline{Q}}/\xi]} \LabelRule{\exists R} \UnaRule{A^Q[\tau^{\underline{Q}}/\xi]\vdash \exists\xi A^Q} \LabelRule{\oc R} \UnaRule{A^Q[\tau^{\underline{Q}}/\xi]\vdash \oc{\exists\xi A^Q}} \LabelRule{\wn d R} \UnaRule{A^Q[\tau^{\underline{Q}}/\xi]\vdash \wn{\oc{\exists\xi A^Q}}} \LabelRule{\wn L} \UnaRule{\wn{A^Q[\tau^{\underline{Q}}/\xi]}\vdash \wn{\oc{\exists\xi A^Q}}} \LabelRule{\rulename{cut}} \BinRule{\Gamma^Q\vdash \wn{\oc{\exists\xi A^Q}},\wn{\Delta^Q}} \DisplayProof$ $\AxRule{\Gamma,A\vdash \Delta} \LabelRule{\exists L} \UnaRule{\Gamma,\exists\xi A\vdash \Delta} \DisplayProof \qquad\mapsto\qquad \AxRule{\Gamma^Q,A^Q\vdash \wn{\Delta^Q}} \LabelRule{\exists L} \UnaRule{\Gamma^Q,\exists\xi A^Q\vdash \wn{\Delta^Q}} \LabelRule{\oc d L} \UnaRule{\Gamma^Q,\oc{\exists\xi A^Q}\vdash \wn{\Delta^Q}} \DisplayProof$

### Alternative presentation

It is also possible to define $A^{\underline{Q}}$ as the primitive construction. $\begin{array}{rcl} X^{\underline{Q}} & = & X \\ (A\imp B)^{\underline{Q}} & = & \oc{A^{\underline{Q}}}\limp\wn{\oc{B^{\underline{Q}}}} \\ (A\wedge B)^{\underline{Q}} & = & \oc{A^{\underline{Q}}}\tens\oc{B^{\underline{Q}}} \\ T^{\underline{Q}} & = & \one \\ (A\vee B)^{\underline{Q}} & = & \oc{A^{\underline{Q}}}\plus\oc{B^{\underline{Q}}} \\ F^{\underline{Q}} & = & \zero \\ (\neg A)^{\underline{Q}} & = & \wn{(A^{\underline{Q}})\orth} \\ (\forall\xi A)^{\underline{Q}} & = & \forall\xi \wn{\oc{A^{\underline{Q}}}} \\ (\exists\xi A)^{\underline{Q}} & = & \exists\xi \oc{A^{\underline{Q}}} \end{array}$

If we define $(\Gamma\vdash\Delta)^{\underline{Q}} = \oc{\Gamma^{\underline{Q}}}\vdash\wn{\oc{\Delta^{\underline{Q}}}}$, we have $(\Gamma\vdash\Delta)^{\underline{Q}} = (\Gamma\vdash\Delta)^Q$ and thus we obtain the same translation of proofs.